Asymptomatic morphometric vertebral fractures and its associated factors: A cross-sectional study among adults in a selected urban area in Selangor, Malaysia - Yeap, Swan Sim; Thambiah, Subashini C.; Suppiah, Subapriya; Md Said, Salmiah; Appannah, Geeta; Samsudin, Intan Nureslyna; Zainuddin, Nurunnaim; Zahari Sham, Siti Yazmin; Fen, Lee Hew (Public Library of Science, 2021)
Objective: This study aimed to determine the prevalence of vertebral fractures (VF) in a selected urban population in Malaysia and to explore possible variables associated with VF in the study population. Methods: A cross-sectional study involving community-living, healthy subjects aged between 45–90 years from the state of Selangor, Malaysia, were invited to attend a bone health check-up. Subjects with diseases known to affect bone metabolism or were on treatment for osteoporosis (OP) were excluded. Bone mineral density (BMD) was measured using dual energy X-ray absorptiometry (DXA). Lateral and antero-posterior view lumbar spine x-rays were performed and VF was determined by the semi-quantitative Genant method. Results: A total of 386 subjects were studied. Asymptomatic morphometric VF were found in 44 (11.4%) subjects. T12 was the most common vertebrae to be fractured. The prevalence of VF was significantly higher in menopausal women (12.4%) compared to non-menopausal women, in those above the age of 60 (18.5%), in those of Chinese ethnicity (16.5%), in those with a low body fat percentage (17.1%) and among those with OP (27.0%). The mean (standard deviation) 25-hydroxyvitamin D [25(OH)D] levels were significantly higher in those with VF compared to those without VF, 67.64 (23.50) and 57.47 (21.71) nmol/L, respectively. However, after multiple regression analysis, age over 60 years and OP on DXA BMD measurement were the only significant associated factors for VF. Conclusion: Overall, 11.4% of a selected Malaysian urban population had asymptomatic morphometric VF. Age over 60 years and OP on DXA BMD measurement, but not 25(OH)D levels, were associated with VF.